GABA System Modifications During Periods of Hormonal Flux Across the Female Lifespan - Gilfarb, Rachel A.; Leuner, Benedetta (Frontiers in Behavioral Neuroscience, 2022)
The female lifespan is marked by periods of dramatic hormonal fluctuation. Changes in the ovarian hormones estradiol and progesterone, in addition to the progesterone metabolite allopregnanolone, are among the most significant and have been shown to have widespread effects on the brain. This review summarizes current understanding of alterations that occur within the GABA system during the major hormonal transition periods of puberty, the ovarian cycle, pregnancy and the postpartum period, as well as reproductive aging. The impact of altered inhibitory activity on brain function and behavior during these times are also discussed. Lastly, avenues for future research are identified, which, if pursued, can broaden understanding of the GABA system in the female brain and potentially lead to better treatments for women experiencing changes in brain function at each of these hormonal transition periods.